Pengolahan Jamu Berbahan Dasar Telang sebagai Upaya Peningkatan Imunitas di Desa Siwalan Kecamatan Sawahan Kabupaten Nganjuk: Processing of Telang-Based Herbal Medicine as an Effort to Increase Immunity in Siwalan Village, Sawahan District, Nganjuk Regency - Krismiratsih, Fitri; Fibriani, Suwinda; Rahmadhani, Ika Puspitasari Dyah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Herbal medicine is a traditional medicine that has proven effective in maintaining and overcoming health problems. Currently, consuming herbal medicine is a trend in maintaining the body's immune system. One of the natural ingredients used is the butterfly pea flower, which grows abundantly in the yards of residents of Siwalan Village, Sawaahan District, Nganjuk Regency. This community service activity targets the local Family Health Empowerment (PKK) group so that members are motivated to utilize butterfly pea plants as herbal medicine ingredients and business opportunities. The activity was conducted through counseling, direct practice, and interactive discussions. Participants were very enthusiastic about participating in the activity and actively participated. The evaluation results showed increased participant understanding from an average of 1.2 - 2.2 before the activity to 1 - 4.5 after the activity. This shows a significant increase in participant knowledge and skills. In this activity, participants learned about the benefits, processing methods, and increasing the economic value of butterfly pea plants. In addition, participants also learned about business opportunities from butterfly pea raw materials to create entrepreneurial activities in the local environment.